Answer:
. This is the solution.
Explanation:
The homogeneous differential equation is given by
![(dy)/(dx) = (x^(2) + y^(2) )/(2xy)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xpdr0z8cgsmqpa0rqu29fft4w00v3tuek6.png)
⇒
........ (1)
Now to solve this differential equation we assume that y = vx where v is another variable.
So, differentiating with respect to x we get
![(dy)/(dx) = v + x (dv)/(dx)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/82gjoha1dkqkl6qh90866iuwmy6oxxdler.png)
Therefore, the above equation (1) becomes
{Since
}
⇒
![x(dv)/(dx) = (1 + v^(2) - 2v^(2) )/(2v)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/w2q4hzl24pdx7x4l0svth9ayntxyqybguo.png)
⇒
![x(dv)/(dx) = (1 - v^(2))/(2v)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mzh0gc9jk1a4zkkt19a1ik5gmuj5ezq3bs.png)
⇒
{By separation of variables}
Now, integrating both sides we get,
![\int {(2v)/( 1- v^(2))} \, dv = \int {(dx)/(x) } \, dx](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7yiur66rmn1bt63x39zhvvpwedl0zgvp1o.png)
⇒
![- \int {(d(1 - v^(2) ))/(1 - v^(2))} = \int {(dx)/(x) }](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jmxurcgz5l81dif68xfsm32d25108ye5wh.png)
⇒
{Where c is the integration constant}
⇒
(Answer)